Poor but spirited in Karimnagar: field notes of a civil servant - Dawra, Sumita (New Delhi, 2012)
This book is about cover diverse populations, from child labour to cotton farmers, from coal miners to malnourished power loom weavers.
Keywords: Civil servant-Field notes